Variations of aquaculture structures, operations, and maintenance with increasing ocean energy - Heasman, Kevin G.; Scott, Nicholas; Sclodnick, Tyler; Chambers, Michael; Costa-Pierce, Barry; Dewhurst, Tobias; Isbert, Wolf; Buck, Bela H. (Frontiers in Aquaculture, 2024)
Aquaculture in exposed and/or distant ocean sites is an emerging industry and field of study that addresses the need to improve food security along with the challenges posed by expansion of urban and coastal stakeholders into nearshore and sheltered marine waters. This move necessitates innovative solutions for this industry to thrive in high-energy environments. Some innovative research has increased understanding of the physics, hydrodynamics, and structural requirements enabling the development of appropriate systems. The blue mussel (Mytilus edulis), the New Zealand green shell or green lipped mussel (Perna canaliculus), and the Pacific Oyster (Magallana gigas), are the primary targets for commercial exposed bivalve aquaculture. Researchers and industry members are actively advancing existing structures and developing new structures and methodologies for these and alternative high-value species suitable for such conditions. For macroalgae (seaweed) cultivation, such as sugar kelp (Saccharina latissimi), oar weed (Laminaria digitata), or kelp sp. (Ecklonia sp.), longline systems are commonly used, but further development is needed to withstand fully exposed environments and improve productivity and efficiency. In marine finfish aquaculture, three primary design categories for open ocean net pens are identified: flexible gravity pens, rigid megastructures, closed pens, and submersible pens. As aquaculture ventures into more demanding environments, a concerted focus on operational efficiency is imperative. This publication considers the commercial and research progress relating to the requirements of aquaculture’s expansion into exposed seas, with a particular focus on the cultivation of bivalves, macroalgae, and marine finfish cultivation technologies and structural developments.